Investigating the effect of Curcumin on Long Noncoding RNAs NUTM2A-AS1 and HCG18 expression changes in Hepatocellular Carcinoma (HCC): Curcumin on Hepatocellular Carcinoma (HCC) - Alavian, Seyed Ehsan; Salehipour, Masoud; Zaker Bostanabad, Saeed; Tafvizi, Farzaneh; Heiat, Mohammad (Iranian Journal of Pharmaceutical Sciences, 2023)
Hepatocellular carcinoma (HCC) is a common tumor in liver tissue. The lack of molecular markers for the diagnosis and evaluation of treatment methods is noticeable despite the progression of HCC diagnostic and treatment methods; therefore, the present study aimed to find molecular markers with key roles in the initiation and progression of HCC and investigate the impact of curcumin on their expression. To this end, bioinformatics studies were conducted to candidate two long noncoding RNAs (lncRNAs) related to HCC, which interacted with the highest number of microRNAs (NUTM2A-AS1 and HCG18), and five microRNAs (hsa-miR-15a-5p, hsa-miR-15b-5p, hsa-miR-16-5p, hsa-miR-195-5p, and hsa-miR-424-5p), which interacted with most lncRNAs among candidate lncRNAs. Afterward, their expression was measured in hepG2 cancer cells and fibroblast cells treated with curcumin compared to the untreated samples. The expression of miRNAs and lncRNAs at half inhibition concentrations (IC50) of curcumin indicated that curcumin significantly increased the expression of miR-195, miR-15a/16, and miR-424 and reduced the expression of miR-15b-5P, NUTM2A-AS1 lncRNA, and HCG18 in comparison with a control group (P≤0.05). Obtained data showed that curcumin increases the expression of anti-cancer genes, miR-195, miR-15a/16, and miR-424, and decreases the activity of cancerous genes, miR-15b-5P, NUTM2A-AS1 lncRNA, and HCG18; therefore, it can be used as an anti-cancer agent in the treatment of HCC.